Clopidogrel and Aspirin Resistance and Its Interaction with Peripheral Arterial Disease Outcomes in the Indian Population - Vikram Patra; Rohit Mehra; C V N M Dattatraya; Rishi Dhillan; Anuka Sharma; Varun Sharma; Brijesh Biswas; Ajay Kumar Dabas; Rahul Merkhed (Indian Journal of Vascular and Endovascular Surgery)
Objectives: The objective of the study was to ascertain adverse events (major adverse cardiac and limb events) events in patients of established peripheral arterial disease (PAD), on clopidogrel and aspirin antiplatelet therapy. Patients and Methods: Patients aged 18 years or over, with PAD were screened for participation in the study. Patients were considered to have symptomatic PAD if they met either of two criteria: a history of intermittent claudication, rest pain, or tissue loss of presumed atherosclerotic origin, with either ankle–brachial index <0.85, previous leg amputation, peripheral vascular surgery, or percutaneous intervention; or angiographic or computed tomographic imaging of significant lower-extremity occlusive atherosclerotic disease. The patients took clopidogrel and aspirin at a dose ≥75 mg/day for at least 4 weeks before enrolment. Those with contraindications to antiplatelet usage were excluded from the study. Blood was used as genotyping material. Patient samples were genotyped for clopidogrel resistance (CR)-associated single-nucleotide polymorphism (SNPs) using Illumina Global Screening Array Ver 3 Bead Chip. Illumina Infinium Genotyping Assay protocol was implemented. Intensities of the beads’ fluorescence were detected using iScan Reader (Illumina Inc). Aspirin resistance (AR) was determined with the whole blood, point of care, turbidimetric cartridge-based method, platelet aggregation, and VerifyNow P2Y12 assay, and results were reported in platelet reactivity units (PRU), at a cutoff of 550 PRU. Results: The mean age was 58.4 (12.6) years with 90% males. The mean body mass index was 22.57 (3.54) kg/m2. The cohort comprised 58.9% smokers, 42% alcoholics, 33.5% diabetics, and 63% hypertensives. Limited efficacy of clopidogrel was observed in 52.38% of patients with loss of function (LOF) variations in the CYP2C19 gene. The mean duration of follow-up was 13.4 (4.7) months. Subjects with CYP2C19 LOF alleles showed more complications (39%) and the relationship between the LOF variation in the CYP2C19 gene and the adverse clinical outcomes (major adverse cardiac events [MACE] and major adverse limb events [MALE]) was found to be statistically significant (P = 0.11). CR and AR were found in 147 (50.3%) and 69 (23%) patients, respectively. Resistance to both the antiplatelets was found in 41 (14%) patients. Conclusion: In this largest observational study, the use of dual antiplatelet therapy in the Indian population with PAD on the MACE and MALE events was higher in the patients with CYP2C19 LOF alleles. The study found a statistically significant relationship between genetic testing results and clinical outcomes.